SUBDURAL HYGROMA PRESENTING AS DEMENTIA WITH KLUVER-BUCY SYMPTOMS - Duggal, Harpreet S. (Medknow Publications, 1999)
Dementia is not an uncommon presentation in psychiatric practice. Of the various causes of reversible dementia, subdural hygroma is a lesser-known potentially reversible cause. A case of dementia with Kluver-Bucy symptoms secondary to subdural hygroma is described and implications of Kluver-Bucy symptoms in dementia are discussed.